Effect of biochar on reclaimed tidal land soil properties and maize (Zea mays L.) response. (January 2016) - Kim, Hyuck-Soo; Kim, Kwon-Rae; Yang, Jae E.; Ok, Yong Sik; Owens, Gary; Nehls, Thomas; Wessolek, Gerd; Kim, Kye-Hoon
Highlights: Biochar amendment reduced ESP and increased the water stable aggregate percentage. Increases in the percentage water stable aggregate enhanced maize growth. Biochar decreased maize Na uptake resulting in decreased salt stress. Biochar was a beneficial amendment for reclaimed tidal land. Abstract: Reclaimed tidal land soil (RTLS) often contains high levels of soluble salts and exchangeable Na that can adversely affect plant growth. The current study examined the effect of biochar on the physicochemical properties of RTLS and subsequently the influence on plant growth performance. Rice hull derived biochar (BC) was applied to RTLS at three different rates (1%, 2%, and 5% (w/w)) and maize ( Zea mays L.) subsequently cultivated for 6 weeks. While maize was cultivated, 0.1% NaCl solution was supplied from the bottom of the pots to simulate the natural RTLS conditions. Biochar induced changes in soil properties were evaluated by the water stable aggregate (WSA) percentage, exchangeable sodium percentage (ESP), soil organic carbon contents, cation exchange capacity, and exchangeable cations. Plant response was measured by growth rate, nutrient contents, and antioxidant enzyme activity of ascorbate peroxidase (APX) and glutathione reductase (GR). Application of rice hull derived biochar increased the soil organic carbon content and the percentage of WSA by 36–69%, while decreasing the ESP. The highest dry weight maize yield was observed from soil which received 5% BC (w/w), which was attributed to increased stability of water-stable aggregates and elevated levels of phosphate in BC incorporated soils. Moreover, increased potassium, sourced from the BC, induced mitigation of Na uptake by maize and consequently, reduced the impact of salt stress as evidenced by overall declines in the antioxidant activities of APX and GR.